Use of Clear Aligners with a Surgery-First Approach for Treatment of the Anterior Open Bite: A Systematic Review and Comparison with Conventional Fixed Appliances - Joshua Stewart, DMD; Marshall F. Newman, DMD, FAAP (Elsevier, 2024)
OBJECTIVES: To complete a systematic review of the use of clear aligner therapy (CAT) when employing a surgery-first approach (SFA) to management of patients with an anterior open bite. To determine in patients undergoing surgery-first orthognathic surgery for treatment of an anterior open bite, is the use of clear aligners, compared to conventional fixed orthodontic appliances, as effective in the management of the anterior open bite with the primary outcome being residual anterior open bite. To provide a patient example demonstrating the use of SFA to orthognathic surgery and CAT approach to orthodontic management of an anterior open bite. METHODS: A systematic review of the literature was undertaken for evaluation of available literature using the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P). Boolean operators "(clear aligner) AND (anterior open bite)", "(clear aligner) AND (surgery-first)," and "(clear aligner) AND (orthognathic surgery)" were used. PRISMA flow diagram was used to identify, screen, and determine studies to be included in the review. The LEGEND Evidence Evaluation Tool was used to help evaluate validity, reliability and applicability and determine the evidence levels of each individual study. Studies that reported the use of CAT for management of anterior open bite without orthognathic surgery were not included. Studies that reported CAT in a surgery-first approach to manage patients without an anterior open bite were not included. RESULTS: 2 studies were included in this systematic review that reported the use of CAT in a surgery-first approach specifically for management of anterior open bite. One study, a retrospective study of 12 patients, found no residual anterior open bite at a 1 year of post-orthodontic follow up. The second, a case study, implemented twenty clear-aligner trays designed for crossbite correction and for passive movements post-operatively which, at the end of treatment, also functioned as 'active retainers' helping to prevent the relapse of the open bite. CONCLUSIONS: The literature supports that CAT is as effective as traditional fixed orthodontic appliances when used in a surgery-first approach. Similarly, there is a body of evidence that supports the use of CAT to treat anterior open bite non-surgically. Based on the findings of this systematic review, there is growing supportive evidence to suggest that CAT can be used in a surgery-first approach to achieve predictable results specifically in management of the anterior open bite. IMPLICATIONS: Clear aligners have obvious advantages compared with fixed appliances in terms of quality of life and esthetics and can be used following orthognathic surgery to correct an anterior open bite.